Self-repairing enamel coating for reinforcing steel bar and preparation method of self-repairing enamel coating

By introducing microcapsules with core-mass-shell structures into the enamel coating, the problem of prone to cracks in long-term use of the coating is solved, and the self-healing function is achieved in an alkaline environment, which significantly improves the corrosion resistance and service life of the coating.

CN119735969AActive Publication Date: 2025-04-01浣江实验室 +1

Patent Information

Application Number
CN202411407725.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2025-04-01
Estimated Expiration
2044-10-10

AI Technical Summary

Technical Problem

Existing enamel coatings are prone to cracks during long-term use and cannot be repaired by themselves, resulting in a degradation of protective performance, especially in the protection of building materials such as steel bars.

Method used

Microcapsules with a three-layer structure of core-mass-shell. The shell layer of the microcapsules is made of silica material. The mass layer is made of boron nitride, alumina and other materials. The core layer wraps the repair agent to ensure that the structure is stable and the self-healing function is achieved under an alkaline environment.

Benefits of technology

It significantly improves the corrosion resistance and service life of the coating, can automatically repair cracks in alkaline environments, extend the service life of steel bars, and improves the safety and stability of building structures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119735969A_ABST
    Figure CN119735969A_ABST
Patent Text Reader

Abstract

The invention discloses a self-repairing enamel coating for reinforcing steel bars, the self-repairing enamel coating comprises an enamel substrate and a microcapsule, the microcapsule comprises a shell layer, and the shell layer is prepared from 10-20 parts of tetraethoxysilane, 15-30 parts of ethanol, 1-5 parts of ammonia water and 10-20 parts of water; the mass layer is positioned on the inner side of the shell layer and is selected from one or two or more of boron nitride, aluminum oxide, zirconium oxide, titanium dioxide, magnesium oxide or silicon carbide; and the core layer is positioned on the inner side of the mass layer and is made of sodium silicate, zirconium silicate, calcium silicate, calcium titanate or barium titanate. The invention further discloses a preparation method of the self-repairing enamel coating for the reinforcing steel bar. The microcapsule is introduced into the enamel coating, so that the service life of the coating is remarkably prolonged. The enamel coating with the self-repairing capability can repair microcracks and damages generated in the using process of the coating in time, and further erosion of corrosive media is prevented, so that the service life of base materials such as reinforcing steel bars is prolonged, and the safety and stability of a building structure are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ceramic coatings and self-repairing materials, and in particular relates to a self-repairing enamel coating for steel bars and a preparation method thereof. Background Art

[0002] In the field of materials science, enamel coatings have been widely used in many industrial fields such as construction, chemical industry, and energy due to their excellent hardness, wear resistance, corrosion resistance, and high-temperature stability. As a protective coating, enamel coatings can effectively isolate external corrosive media, especially in high temperature and acid-base environments. However, the inherent brittleness of enamel materials and their high sensitivity to crack propagation have become the main bottlenecks limiting their service life and protective effects. Once microcracks appear in the enamel coating, external media can easily penetrate into the substrate through the cracks, causing the coating to fail. This not only affects the protective performance of the coating, but can even threaten the structural safety of the protected material.

[0003] In recent years, self-healing materials, as an emerging smart material, have been widely studied and applied in the field of coating technology. Self-healing materials can automatically repair cracks or damage after being damaged through internal repair mechanisms, thereby restoring their original mechanical and protective properties. In the application of enamel coatings, microcapsule technology is widely regarded as one of the effective methods to achieve self-healing. Microcapsules encapsulate the repair agent in the shell layer. When the coating is damaged, the microcapsules rupture and release the repair agent, thereby filling the cracks and restoring the coating performance. The application of this technology not only improves the service life of the coating, but also maintains long-term protective performance in relatively harsh environments.

[0004] Despite this, most enamel coatings currently do not have self-repairing functions. Once cracks appear during long-term use, they cannot repair themselves. This problem is particularly prominent in the protection of building materials such as steel bars. As an important part of the building structure, steel bars are often exposed to the natural environment and are easily damaged by corrosive substances such as acids, alkalis, and salts. The generation of cracks will further accelerate the corrosion of steel bars, seriously threatening the safety and stability of the building structure.

[0005] In response to this problem, several patents have proposed partial solutions. For example, Chinese patent CN108531908A discloses a metal anticorrosion coating with a double-layer structure, which mainly solves the problem of thermal expansion coefficient mismatch between the coating and the metal substrate, and improves the service life of the anticorrosion coating, but the self-repairing function of the coating is less mentioned, and the long-term protection problem caused by crack expansion cannot be effectively solved. CN202410314291 discloses a method for preparing an acid-alkali-salt enamel coating. Although the corrosion resistance of the coating is improved to a certain extent, its production process is complicated and the cost is high, and it is difficult to achieve large-scale application. CN202410377987 significantly enhances the self-repairing performance of concrete by introducing polymer microcapsule technology, but the stability and repair effect of this technology in a strong alkaline environment still need to be improved. In addition, Chinese patent CN118599379A discloses a self-repairing super-hydrophobic nano anticorrosion coating, which realizes the self-repairing function by adding microcapsules to the coating. Although the protective effect of the coating is improved, the hydrophobic performance after self-repair decreases, affecting its reliability in long-term use.

[0006] Traditional microcapsule technology mostly adopts a core-shell structure, which often has limitations in its application in complex or extreme environments. In a strong alkaline environment, the shell structure of the core-shell microcapsule is relatively fragile and prone to rupture, resulting in premature leakage of the repair agent and inability to effectively repair the coating. At the same time, the release mechanism of existing microcapsules is relatively simple, and it is difficult to achieve precise control according to the degree of coating damage, which further limits the adaptability of self-healing coatings in different application scenarios. Summary of the invention

[0007] In order to overcome the shortcomings of the prior art, the present invention provides a self-repairing enamel coating for steel bars and a preparation method thereof. The coating is loaded with microcapsules, which have a core-matter-shell structure. The microcapsules are dispersed in the enamel matrix, so that it has a self-repairing function under alkaline conditions. The preparation method significantly improves the corrosion resistance and service life of the coating, and is particularly suitable for industrial applications in harsh environments, such as anti-corrosion protection of building structures.

[0008] The technical solution adopted by the present invention to solve the technical problem is: a self-repairing enamel coating for steel bars, comprising:

[0009] Enamel substrate and microcapsules, the microcapsules comprising:

[0010] The shell layer is prepared by comprising 10-20 parts of tetraethoxysilane, 15-30 parts of ethanol, 1-5 parts of ammonia water, and 10-20 parts of water;

[0011] The material layer is located inside the shell layer and is made of one or two or more of boron nitride, aluminum oxide, zirconium oxide, titanium dioxide, magnesium oxide or silicon carbide;

[0012] The core layer is located inside the texture layer and is made of sodium silicate, zirconium silicate, calcium silicate, calcium titanate or barium titanate.

[0013] During the preparation of the shell layer, a sol-gel reaction is used to generate a shell material with high-temperature stability. During the preparation of the core layer, heating treatment is performed to ensure that the material can be completely volatilized during high-temperature calcination to reduce the impact on the coating structure. During the preparation of the core layer, the stirring speed needs to be controlled at 200-600RPM to ensure that the microcapsules are uniform in size and to avoid leakage of the core layer material.

[0014] Furthermore, the enamel matrix includes 23-28 parts of phosphorus pentoxide, 15-20 parts of aluminum oxide, 10-15 parts of sodium oxide, 10-14 parts of potassium oxide, 8-15 parts of boron trioxide, 5-10 parts of calcium fluoride, 5-10 parts of lithium oxide, 5-10 parts of silicon dioxide, 2-5 parts of calcium oxide, 1-3 parts of nickel oxide, 1-3 parts of cobalt oxide and 1-3 parts of zirconium dioxide.

[0015] The shell of the microcapsule is made of silica sol, which is specifically prepared by tetraethoxysilane (TEOS), ethanol, ammonia water as an alkaline catalyst and water. It has good high-temperature stability, ensuring that it remains intact during the high-temperature calcination process of the enamel coating.

[0016] The material layer of the microcapsule is located between the shell layer and the core layer, has good thermal stability, and is completely volatilized during the calcination process, ensuring that the overall performance of the coating is not affected.

[0017] The repair agent is used as the core material to destroy the microcapsule shell when the enamel is corroded by alkaline and release the repair agent in the capsule core to repair the damaged part of the enamel. The core material needs to have good chemical stability to ensure that the repair agent can be effectively released when the coating is damaged. The selected polymer should have good biocompatibility and environmental adaptability, and ensure that it can still maintain its integrity under strong alkaline conditions, play a repair function, and provide the enamel with self-repair ability in an alkaline environment. The above material selection meets the above conditions.

[0018] Furthermore, the reaction temperature for preparing the shell layer is 25-30°C; the reaction temperature for preparing the mass layer is 200-300°C; and the reaction temperature for preparing the core layer is 60-70°C.

[0019] Furthermore, the coating thickness is 300-500 microns.

[0020] Furthermore, it exhibits self-repairing function in an alkaline environment.

[0021] Furthermore, the microcapsules are uniformly dispersed in the enamel matrix, and the content ratio of the microcapsules to the enamel matrix is ​​5-15%.

[0022] The present invention also discloses a method for preparing a self-repairing enamel coating for steel bars, comprising the following steps:

[0023] Preparation of microcapsules: 10-20 parts of tetraethoxysilane are added to a reactor, 15-30 parts of ethanol are slowly added, and stirred evenly; 1-5 parts of ammonia water are gradually added as an alkaline catalyst, the reaction temperature is controlled at 25-30°C, and the reaction time is 4 hours, so that the silica sol forms a shell layer of the microcapsules;

[0024] Mix 5-15 parts of boron nitride, 10-20 parts of aluminum oxide and 5-15 parts of zirconium oxide in proportion, gradually add them to the shell material, stir evenly, and heat at 200-300°C;

[0025] Add 10-20 parts of sodium silicate, 10-20 parts of zirconium silicate and 10-20 parts of barium titanate into the reactor, heat to 60-70°C, and wrap the repair agent in the shell layer by interfacial polymerization technology to form a core-matter-shell structure microcapsule;

[0026] Preparation of the enamel matrix: 23-28 parts of phosphorus pentoxide, 15-20 parts of aluminum oxide, 10-15 parts of sodium oxide, and 10-14 parts of potassium oxide matrix raw materials are mixed according to proportion, and an appropriate amount of deionized water is added, and stirred evenly;

[0027] The prepared microcapsule material is evenly dispersed in the enamel matrix, ensuring thorough mixing.

[0028] Furthermore, in the step of preparing the microcapsules with a core-mass-shell structure, the stirring speed is 200-600RPM.

[0029] The prepared enamel coating is evenly applied to the surface treated steel bars. Commonly used methods include dipping, spraying or brushing. The specific coating method is selected according to the required coating thickness and coating uniformity. The coating thickness should be controlled at 300 to 500 microns to ensure good mechanical strength and corrosion resistance during application.

[0030] The mixture is poured into a mold and calcined at 800-900°C for 30 minutes to ensure that the enamel coating is fully cured and that the microcapsules remain structurally stable at high temperatures, while giving the coating self-healing capabilities under alkaline conditions.

[0031] After calcination, the steel bar should be slowly cooled to room temperature to prevent thermal stress caused by sudden temperature change, which may lead to cracking of the coating. According to actual needs, surface passivation or other protective treatments can also be performed to enhance the durability and corrosion resistance of the steel bar surface coating.

[0032] Through the above steps, the enamel coating provided by the present invention can not only maintain excellent mechanical strength and durability under high-temperature calcination conditions, but also has the function of automatically repairing damaged areas in an alkaline environment. It is suitable for the anti-corrosion protection of building materials such as steel bars and can significantly extend their service life.

[0033] In order to solve the problems mentioned in the background technology, the present invention proposes a polymer microcapsule with a core-matter-shell three-layer structure, and its application in the self-repair technology of enamel coating can significantly improve the protective effect and durability of the coating. The microcapsule wraps the repair agent through the core layer, the material layer provides protection and release control, and the shell layer ensures that the microcapsule still has a high structural integrity under extreme environments. Compared with traditional core-shell microcapsules, core-matter-shell microcapsules not only have stronger corrosion resistance and environmental adaptability, but also can accurately release the repair agent according to changes in the external environment and the degree of damage, thereby improving the self-repair effect of the coating.

[0034] The present invention optimizes the design of the microcapsule structure to enable it to remain stable in a strong alkaline environment, and is particularly suitable for the protection of key building materials such as steel bars. The self-repairing microcapsules in the enamel coating can promptly repair microcracks caused by external forces or the environment, and prevent the corrosive medium from penetrating into the surface of the steel bars, thereby extending the service life of the steel bars and improving the safety of the building structure. This has important practical significance for the sustainable development of the construction field.

[0035] The enamel coating of the present invention adopts a core-matter-shell three-phase structure of microcapsules, which provides stronger structural stability compared to traditional enamel coatings. This three-layer structure of microcapsules can effectively resist external mechanical forces and chemical erosion, reduce the breakage rate of microcapsules during use, and thus improve the overall durability and reliability of the enamel coating.

[0036] The core-matrix-shell structure gives the microcapsules better environmental responsiveness, and can precisely control the release of the repair agent when the enamel is damaged in a strong alkaline environment. This controllability ensures that the repair agent is activated only when the enamel coating is damaged, improving the repair efficiency and the service life of the material, allowing the enamel coating to self-repair in a timely and effective manner.

[0037] The microcapsule shell layer is made of silica material, which exhibits excellent stability at high temperatures. The enamel coating of the present invention is calcined at high temperatures during the preparation process. The silica shell layer ensures the integrity of the microcapsules during the coating preparation process, avoiding premature rupture or failure of the repair agent caused by high temperature, thereby ensuring that the enamel coating can still maintain good performance in a high temperature environment.

[0038] The polymer material used in the core layer not only has good chemical stability, but also has biocompatibility and environmental adaptability. This allows the enamel coating to maintain its repair function in a strong alkaline environment, broadens the application range of the enamel coating, and enables it to function stably in various complex environments.

[0039] By introducing the microcapsules of the present invention into the enamel coating, the service life of the coating is significantly improved. The enamel coating with self-repairing ability can timely repair microcracks and damage generated in the coating during use, prevent further erosion by the corrosive medium, thereby extending the service life of the substrate such as steel bars and improving the safety and stability of the building structure. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 This is a schematic diagram of the self-repairing process of the enamel coating containing the self-repairing capsules under alkaline conditions of the present invention. DETAILED DESCRIPTION

[0041] In order to enable those skilled in the art to better understand the solutions of the present invention, the following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0042] Example 1

[0043] A self-repairing enamel coating for steel bars comprises: an enamel substrate and microcapsules, wherein the microcapsules comprise a shell layer, the preparation ingredients of which include 10-20 parts of tetraethoxysilane, 15-30 parts of ethanol, 1-5 parts of ammonia water, and 10-20 parts of water; a material layer located inside the shell layer, and comprising one or two or more of boron nitride, aluminum oxide, zirconium oxide, titanium dioxide, magnesium oxide, or silicon carbide; and a core layer located inside the material layer, and comprising sodium silicate, zirconium silicate, calcium silicate, calcium titanate, or barium titanate.

[0044] The enamel matrix includes 23-28 parts of phosphorus pentoxide, 15-20 parts of aluminum oxide, 10-15 parts of sodium oxide, 10-14 parts of potassium oxide, 8-15 parts of boron trioxide, 5-10 parts of calcium fluoride, 5-10 parts of lithium oxide, 5-10 parts of silicon dioxide, 2-5 parts of calcium oxide, 1-3 parts of nickel oxide, 1-3 parts of cobalt oxide and 1-3 parts of zirconium dioxide.

[0045] In this embodiment, the content ratio of microcapsules to enamel matrix is ​​8%.

[0046] The coating material is calcined at high temperature, and the microcapsules maintain their structural stability, ensuring that the coating has the function of automatic repair in an alkaline environment, significantly improving the anti-corrosion performance of the coating.

[0047] Before coating, the steel bar surface needs to be pre-treated to ensure that the coating can adhere firmly. Common surface treatment steps include:

[0048] Cleaning: Use a degreaser, acid solution or alkaline solution to clean the surface of the steel bar to remove grease, oxides, rust and other contaminants.

[0049] Pickling: Remove surface rust by pickling (such as using dilute sulfuric acid or hydrochloric acid), clean and rinse.

[0050] Surface passivation: Treat with a passivator (such as phosphoric acid or passivating liquid) to reduce the activity of the steel surface and increase the adhesion of the coating.

[0051] A method for preparing a self-repairing enamel coating for steel bars comprises the following steps:

[0052] 1) Steel bar surface treatment:

[0053] First, cut the steel bar with a diameter of 10 mm into 1-meter-long specimens. In order to ensure good adhesion of the coating, the surface of the steel bar needs to be thoroughly cleaned. Use a degreaser to clean the surface of the steel bar to remove oil and impurities. After cleaning, immerse the steel bar in a 10% dilute sulfuric acid solution for 30 minutes to effectively remove oxides and rust on the surface of the steel bar. After pickling, rinse the surface thoroughly with clean water. Next, immerse the steel bar in a phosphoric acid solution for passivation for 5 minutes. This step can reduce the activity of the steel bar surface and increase the adhesion of the coating. After passivation, the steel bar needs to be dried for use.

[0054] 2) Preparation of microcapsule shell:

[0055] In order to enhance the self-healing function of the coating, microcapsule technology is used. 15 parts of tetraethoxysilane (TEOS), 25 parts of ethanol, 3 parts of ammonia water and 15 parts of water are added to the reactor in sequence, stirred at 28°C, and the reaction time is 4 hours. In this process, the generated silica sol forms a microcapsule shell with high temperature stability, which can remain intact during the subsequent high-temperature calcination process, ensuring the stability of the coating.

[0056] 3) Preparation of the texture layer:

[0057] In order to ensure that the microcapsules can play a self-repairing role in a high temperature environment, 10 parts of boron nitride, 15 parts of aluminum oxide, and 10 parts of zirconium oxide are mixed in proportion, gradually added to the prepared shell material, and stirred evenly. The layer material is then heated at 250°C for 1 hour to ensure that the layer material can be completely volatilized during the high-temperature calcination process to reduce the impact on the coating structure.

[0058] 4) Preparation of nuclear layer:

[0059] Next, 15 parts of sodium silicate, 15 parts of zirconium silicate and 15 parts of barium titanate were stirred at 65°C at a stirring speed of 200-600RPM, and the repair agent was encapsulated in the shell layer using interfacial polymerization technology to form a core-matter-shell three-layer structure microcapsule. This process step requires a uniform stirring speed to prevent leakage of the core layer material. The prepared microcapsules were dried at 100°C and sieved to obtain microcapsule products with uniform particle size.

[0060] 5) Preparation and coating of enamel substrate:

[0061] 25 parts of phosphorus pentoxide, 18 parts of aluminum oxide, 12 parts of sodium oxide, 12 parts of potassium oxide, 10 parts of boron trioxide, 8 parts of calcium fluoride, 6 parts of lithium oxide, 7 parts of silicon dioxide, 3 parts of calcium oxide, 2 parts of nickel oxide and 2 parts of cobalt oxide were mixed according to the formula to form an enamel matrix slurry. The prepared microcapsules were added to the enamel matrix at 5% of the total weight and stirred evenly to ensure that the microcapsules were evenly distributed. Then, the mixture was evenly coated on the surface of the surface-treated steel bar, and the coating thickness was controlled to be 400 microns.

[0062] 6) High temperature calcination and cooling:

[0063] After coating, the steel bar is placed in a high-temperature furnace and calcined at 850°C for 30 minutes. At this temperature, the enamel coating is fully cured and the structure of the microcapsules is stable, giving the coating self-healing function in an alkaline environment. After calcination, the steel bar needs to be slowly cooled to room temperature to avoid cracking or peeling of the coating due to a sudden drop in temperature.

[0064] The prepared steel bar self-repairing enamel coating by the preparation method of Example 1 not only has excellent anti-corrosion performance, but also can automatically release the repair agent when the coating is slightly damaged, so as to repair the cracks in time and extend the service life of the coating.

[0065] Example 2

[0066] On the basis of Example 1, 5 parts of titanium dioxide were added to the shell layer material of the microcapsule to enhance its high temperature stability. The preparation method of the microcapsule was the same as that of Example 1, and the materials of the core layer and the core layer remained unchanged.

[0067] In this embodiment, 5 parts of titanium dioxide are added to the shell material of the microcapsule. The introduction of titanium dioxide can enhance the mechanical strength and chemical resistance of the microcapsule in a high temperature environment. The reason is that titanium dioxide has excellent heat resistance and stability, which can improve the structural integrity of the shell during the calcination process, thereby avoiding the rupture or damage of the microcapsule shell caused by high temperature. In addition, titanium dioxide can also improve the crack resistance of the shell, so that the microcapsule can maintain its function intact during the calcination process, and ultimately improve the self-repairing performance and anti-corrosion effect of the coating in extreme environments.

[0068] Example 3

[0069] On the basis of Example 1, the layer material is changed to 7 parts of magnesium oxide, 10 parts of aluminum oxide and 5 parts of silicon carbide. The layer material is completely volatilized at high temperature, and it is ensured that the microcapsules will not break during the calcination process. The change of the layer material is intended to improve the volatility of the microcapsules during high-temperature calcination, to ensure that the layer material can be completely volatilized under high temperature conditions, and not to affect the overall structure of the coating. As layer materials, magnesium oxide and silicon carbide have good high temperature resistance and volatility, and can ensure that the layer is stably decomposed during the calcination process. This improvement not only ensures the complete volatilization of the layer, but also enhances the mechanical stability of the coating and reduces the generation of cracks through the addition of silicon carbide, thereby improving the protective effect of the coating.

[0070] Example 4

[0071] In this embodiment, the surface treatment process of the steel bar is adjusted, the pickling time is shortened to 20 minutes, and the passivation time is extended to 10 minutes. By shortening the pickling time, the steel bar surface is prevented from being corroded due to excessive pickling; and extending the passivation time can further enhance the adhesion between the coating and the steel bar surface and improve the durability of the coating. The reason for this improvement is that reasonable control of the pretreatment process of the steel bar surface can not only reduce the defects of the steel bar surface, but also increase the adhesion of the coating, thereby improving the mechanical strength and anti-corrosion effect of the coating.

[0072] Example 5

[0073] In this embodiment, the coating thickness is adjusted from 400 microns to 500 microns. The reason for increasing the coating thickness is that a thicker coating can provide a better physical barrier and reduce the chance of corrosive media entering the steel bar surface through the coating. A thicker coating improves the corrosion resistance and enhances the wear resistance of the steel bar. However, the increase in coating thickness also requires precise control of temperature and time during the calcination process to avoid cracks or peeling caused by excessive coating thickness. Therefore, the improved coating thickness can not only improve the protective performance, but also avoid the problems caused by excessive thickening.

[0074] Example 6

[0075] In this embodiment, barium titanate in the core layer material of the microcapsule is replaced with calcium silicate. Calcium silicate, as a core layer material, has higher chemical stability, especially exhibiting good corrosion resistance in a strong alkaline environment. Calcium silicate can release the repair agent when the microcapsule is broken, and reacts rapidly when in contact with an alkaline medium to form a protective layer, effectively repairing cracks in the coating. Therefore, replacing it with calcium silicate can not only improve the self-repair efficiency, but also enhance the protective effect of the coating in an extremely corrosive environment.

[0076] Example 7

[0077] In this embodiment, the ratio of the material layer is adjusted, specifically a combination of 8 parts of boron nitride, 12 parts of aluminum oxide and 10 parts of zirconium oxide. This ratio adjustment is intended to further enhance the volatility and thermal stability of the material layer material during the calcination process. The increase in the proportion of aluminum oxide helps to enhance the heat resistance of the material layer, while the increase in boron nitride improves the thermal conductivity of the material layer, allowing the coating to volatilize more evenly during high-temperature calcination, ensuring that the material layer material disappears completely. The stability of zirconium oxide provides better mechanical strength for the material layer, avoiding damage to the structure of the microcapsules during the calcination process. This optimization of the ratio further enhances the self-repairing effect and anti-corrosion performance of the coating by enhancing the volatilization and stability of the material layer material, especially being more stable under extreme temperature conditions.

[0078] Example 8

[0079] In this embodiment, the core layer material is adjusted from 15 parts of zirconium silicate and 10 parts of barium titanate to 12 parts of calcium silicate and 15 parts of calcium titanate. The combination of calcium silicate and calcium titanate can provide higher self-healing efficiency. Calcium silicate shows excellent reactivity in alkaline media and can quickly fill cracks. At the same time, the addition of calcium titanate provides stronger structural support and crack resistance for the core layer. Calcium titanate has good chemical corrosion resistance and thermal stability. While repairing cracks, it can also form a solid protective layer to prevent the occurrence of secondary corrosion. This improvement in the core layer material significantly enhances the self-healing effect of the microcapsules in a strong alkaline environment, and the corrosion resistance of the coating has also been further improved, making it suitable for steel structures that are exposed to harsh environments for a long time.

[0080] Comparative Example 1

[0081] In this comparative example, the preparation of the steel enamel coating does not use microcapsule technology, and the other process steps are consistent with Example 1. By comparison, the effect of microcapsules on self-repairing ability and anti-corrosion performance can be evaluated.

[0082] Steel bar surface treatment: Same as Example 1, clean, pickle and passivate the steel bar surface.

[0083] Preparation of enamel matrix: Phosphorus pentoxide, aluminum oxide, sodium oxide, potassium oxide and other matrix raw materials are mixed in proportion, and an appropriate amount of deionized water is added and stirred evenly. Since no microcapsules are used in this comparative example, no microcapsule material is added.

[0084] Coating: Apply the enamel matrix slurry evenly on the treated steel bar surface, and the coating thickness is controlled at 400 microns.

[0085] High temperature calcination: calcined at 850°C for 30 minutes, followed by slow cooling to room temperature.

[0086] In this comparative example, since microcapsules are not used, the self-healing ability of the coating will be significantly reduced. If cracks or damage occur in the enamel coating during use, it will not be able to automatically recover through the self-healing mechanism. In addition, the anti-corrosion performance will also decrease due to the lack of release of the repair agent, especially when exposed to a corrosive environment for a long time, the durability of the coating is poor.

[0087] Comparative Example 2

[0088] In this comparative example, the steel bar was not pickled and passivated, and the other process steps were consistent with Example 1. By comparison, the effect of steel bar surface pretreatment on coating adhesion and corrosion resistance can be evaluated.

[0089] Steel bar surface treatment: Omit the pickling and passivation steps and only perform basic surface cleaning.

[0090] Microcapsule preparation and coating application: As in Example 1, microcapsules were prepared and dispersed in an enamel matrix, and the enamel matrix was coated on the surface of the steel bar, and the coating thickness was controlled at 400 μm.

[0091] High temperature calcination: calcined at 850°C for 30 minutes, followed by slow cooling to room temperature.

[0092] In this comparative example, the pickling and passivation steps of the steel bar surface are omitted, resulting in a significant reduction in the adhesion between the coating and the steel bar surface. During use, the coating is more likely to peel off or hollow, resulting in a decrease in anti-corrosion performance. In addition, steel bars without surface passivation treatment are more likely to corrode in corrosive media, thereby shortening the service life of the coating.

[0093] In order to comprehensively evaluate the anti-corrosion performance and self-repairing effect of the self-repairing enamel coating for steel bars in different embodiments, polarization resistance (Rp) is mainly used as a detection index of anti-corrosion performance. A higher polarization resistance value indicates that the coating has better anti-corrosion ability. The evaluation process first measures the polarization resistance by an electrochemical workstation in conjunction with a three-electrode system. The working electrode is a sample with an enamel coating, the reference electrode is a saturated calomel electrode, and the auxiliary electrode is a platinum electrode. A sodium hydroxide solution with a pH value of 13.4 is used as a corrosive medium to ensure that the steel bar sample is completely immersed in the solution. Then, the test parameters are set by the electrochemical workstation, the scanning range is controlled to be ±10mV to ±20mV near the corrosion potential, and the scanning rate is set to 0.1mV / s or 0.5mV / s, and the polarization curve scan is started. The electrochemical workstation records the changes in sample potential and current, generates a polarization curve, and calculates the polarization resistance (Rp) by analyzing the slope of the linear region of the curve, and uses this to evaluate the anti-corrosion performance of the coating. In order to ensure the reliability of the data, the polarization resistance test of each embodiment is repeated at least three times, and the average value is taken as the final result.

[0094] In addition to the measurement of polarization resistance, self-healing performance is also an important indicator for evaluating coating quality. By creating microcracks on the surface of the coating, the sample is immersed in an alkaline corrosive medium again, and after a certain period of time, the change in its polarization resistance is remeasured. If the self-healing effect of the coating is significant, the polarization resistance should be partially restored to its original state after repair, indicating that the repair agent in the microcapsule is released at the crack and effectively blocks the crack. In addition, wear resistance tests and adhesion tests further verify the mechanical properties of the coating and its firmness of bonding with the substrate. In the wear resistance test, a wear tester is used to simulate the wear of the steel bar during use, and its wear resistance is evaluated by recording the amount of wear of the coating. The adhesion test uses a pull-out tester to test the bonding strength between the coating and the steel bar substrate to ensure that the coating will not peel off or fall off during long-term use.

[0095]

[0096] The above specific implementation modes are used to explain the present invention rather than to limit the present invention. Any modification and change made to the present invention within the spirit of the present invention and the protection scope of the claims shall fall within the protection scope of the present invention.

Claims

1. A self-repairing enamel coating for steel bars, characterized in that: include: Enamel substrate and microcapsules, the microcapsules comprising: The shell layer is prepared by comprising 10-20 parts of tetraethoxysilane, 15-30 parts of ethanol, 1-5 parts of ammonia water, and 10-20 parts of water; The material layer is located inside the shell layer and is made of one or two or more of boron nitride, aluminum oxide, zirconium oxide, titanium dioxide, magnesium oxide or silicon carbide; The core layer is located inside the texture layer and is made of sodium silicate, zirconium silicate, calcium silicate, calcium titanate or barium titanate.

2. The self-repairing enamel coating for steel bars according to claim 1, characterized in that: The enamel matrix includes 23-28 parts of phosphorus pentoxide, 15-20 parts of aluminum oxide, 10-15 parts of sodium oxide, 10-14 parts of potassium oxide, 8-15 parts of boron trioxide, 5-10 parts of calcium fluoride, 5-10 parts of lithium oxide, 5-10 parts of silicon dioxide, 2-5 parts of calcium oxide, 1-3 parts of nickel oxide, 1-3 parts of cobalt oxide and 1-3 parts of zirconium dioxide.

3. The self-repairing enamel coating for steel bars according to claim 1, characterized in that: The reaction temperature for preparing the shell layer is 25-30°C; the reaction temperature for preparing the mass layer is 200-300°C; and the reaction temperature for preparing the core layer is 60-70°C.

4. The self-repairing enamel coating for steel bars according to claim 1, characterized in that: The coating thickness is 300-500 microns.

5. The self-repairing enamel coating for steel bars according to claim 1, characterized in that: It has self-repairing function in alkaline environment.

6. The self-repairing enamel coating for steel bars according to claim 1, characterized in that: The microcapsules are uniformly dispersed in the enamel matrix, and the content ratio of the microcapsules to the enamel matrix is ​​5-15%.

7. A method for preparing a self-repairing enamel coating for steel bars, characterized in that: The following steps are involved: Preparation of microcapsules: 10-20 parts of tetraethoxysilane are added to a reactor, 15-30 parts of ethanol are slowly added, and stirred evenly; 1-5 parts of ammonia water are gradually added as an alkaline catalyst, the reaction temperature is controlled at 25-30°C, and the reaction time is 4 hours, so that the silica sol forms a shell layer of the microcapsules; Mix 5-15 parts of boron nitride, 10-20 parts of aluminum oxide and 5-15 parts of zirconium oxide in proportion, gradually add them to the shell material, stir evenly, and heat at 200-300°C; Add 10-20 parts of sodium silicate, 10-20 parts of zirconium silicate and 10-20 parts of barium titanate into the reactor, heat to 60-70°C, and wrap the repair agent in the shell layer by interfacial polymerization technology to form a core-matter-shell structure microcapsule; Preparation of the enamel matrix: 23-28 parts of phosphorus pentoxide, 15-20 parts of aluminum oxide, 10-15 parts of sodium oxide, and 10-14 parts of potassium oxide matrix raw materials are mixed according to proportion, and an appropriate amount of deionized water is added, and stirred evenly; The prepared microcapsule material is evenly dispersed in the enamel matrix, ensuring thorough mixing.

8. The method for preparing the self-repairing enamel coating for steel bars according to claim 7, characterized in that: In the step of preparing the microcapsules with a core-mass-shell structure, the stirring speed is 200-600RPM.

Citation Information

Patent Citations

  • Metal anticorrosive coating and preparation method and application thereof

    CN108531908A

  • Acid, alkali and salt resistant enamel coating, preparation method thereof and application of acid, alkali and salt resistant enamel coating in cable bridge

    CN118206282A

  • Polymer microcapsule for self-repairing of ultra-high performance concrete and preparation method of polymer microcapsule

    CN118324437A

  • Self-repairing super-hydrophobic nano anticorrosive paint and preparation method thereof

    CN118599379A

  • High-temperature-resistant enamel-based composite coating with self-repairing function, and preparation method thereof

    CN113105115A

Cited By

  • Reusable fire barrier and preparation method thereof

    CN120698770A